1997
DOI: 10.1177/104063879700900312
|View full text |Cite
|
Sign up to set email alerts
|

A 12-Year Retrospective Study of Equine Abortion in Michigan

Abstract: Brief communications 303 perimental placentitis. Bacterial replication occurs in rough endoplasmic reticulum. Am J Pathol 124:226-237. for Brucella abortus strain RB5. Vet Pathol 33:615. [Abstr.] 4. Chitwood MB, Lichtenfels JR: 1972, Identification of parasitic metazoa in tissue sections. Exp Parasitol 32:461-464. 5. Ewalt DR: 1989, Comparison of three culture techniques for the isolation of Brucella abortus from bovine supramammary lymph nodes. J Vet Diagn Invest 1:227-230. 6. Ewalt DR, Payeur JP, Martin MB, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
2
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 8 publications
5
44
2
3
Order By: Relevance
“…Numerous reports from different countries, where the percentage of EHV1 or EHV4 isolation is much higher than the isolation of EAV, confirm this thesis (Szeredi et al 2008, Laugier et al 2011). Often, EAV was not isolated at all during the observed period , Tengelsen et al 1997, Smith et al 2003. However, the investigations conducted from 1977 through 2010 in our laboratory indicate that EAV was the cause of abortion in mares almost as equally often as EHV-1.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Numerous reports from different countries, where the percentage of EHV1 or EHV4 isolation is much higher than the isolation of EAV, confirm this thesis (Szeredi et al 2008, Laugier et al 2011). Often, EAV was not isolated at all during the observed period , Tengelsen et al 1997, Smith et al 2003. However, the investigations conducted from 1977 through 2010 in our laboratory indicate that EAV was the cause of abortion in mares almost as equally often as EHV-1.…”
Section: Discussionmentioning
confidence: 88%
“…EAV and EHV-1/4 are the causes of equine abortion in approximately 10-50% of cases, depending on the authors and horse populations studied (Tengelsen et al 1997, Laugier et al 2011, Bażanów et al 2012. In general, equine herpesvirus-associated abortions are more prevalent than abortions caused by EAV.…”
Section: Discussionmentioning
confidence: 99%
“…EHV-1 induced abortion and death of newborn foals have been shown to occur in Europe with a frequency of 3-25% (Petzoldt et al, 1968;Luttmann et al, 1971;Platt, 1973;Benten et al, 1977;Petzoldt et al, 1987;Pospischil et al, 1992;Pálfi and Christensen, 1995) and in the USA with a frequency of 3-9% Hong et al, 1993;Tengelsen et al, 1997), while in Hungary the abortion rate was found to be 20% (Glávits et al, 1984;Rusvai et al, 1996). We found this infection in 14.9% of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…This places the percentage of abortions for which a cause is not identified more in line with those in other large animal species. 3,16,21,22,25,26,35 Placental insufficiency may result in fetal distress syndrome due to hypoxia to the fetus and/or diminished fetal growth. A possible association of villous hypoplasia and fetal distress syndrome, as defined by defecation of meconium and aspiration of fetal fluids in utero, was beyond the scope of the study presented here.…”
Section: Discussionmentioning
confidence: 99%
“…13,16,25,35 As in the horse, the placenta of alpacas and llamas is epitheliochorial and diffuse, and the maternofetal interface develops synchronously. 11,28,29 This raises the question to whether microanatomic anomalies of the placenta contribute to the large percentage of abortions with undetermined cause in alpacas and llamas.…”
Section: Introductionmentioning
confidence: 99%